Renewable Energies: seeking for a sustainable energy matrix - Dupont, Fabrício Hoff; Grassi, Fernando; Romitti, Leonardo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The current living standards have a dependency and increasing demand for energy, especially electricity, but not limited exclusively to it. However, the supply of power to meet such demand has been unsustainable performed over the years, with people using natural resources as if they were inexhaustible. Recently the common interest of societyhas motivated the development and implementation of renewable-based energy generation systems, and major changes can already be observed worldwide. In this context, this article aims to presentan overview of the main aspects that involve a massive integration of renewable energy sources in the composition of new energy matrices, as well as the paradigm shifts necessary for this new scenario become reality. Finally, some cases of successful implementation of new generation systems, the challenges and the experiences obtained are presented. Moreover, it is also discussed about the incentives that some places in the world offer and the new demands that these places imposes for new construction, with the larger goal of a more sustainable energy consumption andless aggressive to the environment in which we live.